LOVE IN TRANSITION TIMES . THE EDUCATORS OF ADOLESCENTS AMONG CARE , LOVE AND POWER - Riva, Maria Grazia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
By this paper, I want to develop the analysis and the reflection on the problems the educators meet, working with difficult adolescents into the socio-educational services, managing the emotional and love relationships of the young. Authoritarian or punitive interventions, when applied to matters that are highly delicate and complex, are bound to generate consequences that are not always positive or under the control of the educators. If educators are not open to exploring the affective dimensions, they may inadvertently reiterate the abuse that their clients have already undergone. It is necessary to give the right space to the expression of the emotional needs and difficulties of adults, educators, youngsters.